Klub alumni Pravne fakultete v Ljubljani - Koritnik, Boštjan (Pravnik, 2017)
The contribution is a report from the general assembly of the association Klub alumni Pravne fakultete v Ljubljani ("Alumni Association of the Faculty of Law Ljubljana"), which brings together those who gained their education at the Faculty of Law of the University of Ljubljana. New leadership of the association was appointed, with professor at the Faculty of Law Ljubljana Janez Kranjc as the new president.
Keywords: association; društva; poročila; pravne fakultete